Prediksi Angka Kemiskinan Desa Kemang Bejalu Menggunakan Metode Naive Bayes Prediksi Angka Kemiskinan Desa Kemang Bejalu Menggunakan Metode Naive Bayes - Arda Damayanti; Shinta Puspasari; Nazori Suhandi (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2024)
Poverty is one of the problems faced by all countries, especially developing countries such as Indonesia. To find out the extent of poverty in Kemang Bejalu Village, research must be carried out to determine the poverty rate in Kemang Bejalu Village using the Naive Bayes method. The Naive Bayes method is used to classify data and calculate the probability of poverty based on certain factors. This study aims to determine whether the accuracy of the results of the Naive Bayes method can be used in predicting poverty rates. So this confusion matrix calculation obtained an accuracy of 86% of 258 with data for 3 variables, while in testing new test data obtained an accuracy of 90% using the same variables (namely dependents, employment and income). Based on 2022 population data where the poor family is 33% while the well-off family is 67% which is used to produce a poverty rate of 76% of well-off families and 24% of poor families using a test size of 0.4. the prediction process for poverty in Kemang Bejalu village using the Naive Bayes method. So that it can be used by the Kemang Bejalu village government to make a decision.